Chemically Modified Biomimetic Carbon-Coated Iron Nanoparticles for Stent Coatings: In Vitro Cytocompatibility and In Vivo Structural Changes in Human Atherosclerotic Plaques - Akhmedov, Shamil (Biomedicines, 2021)
Atherosclerosis, a systematic degenerative disease related to the buildup of plaques in human vessels, remains the major cause of morbidity in the field of cardiovascular health problems, which are the number one cause of death globally. Novel atheroprotective HDL-mimicking chemically modified carbon-coated iron nanoparticles (Fe@C NPs) were produced by gas-phase synthesis and modified with organic functional groups of a lipophilic nature. Modified and non-modified Fe@C NPs, immobilized with polycaprolactone on stainless steel, showed high cytocompatibility in human endothelial cell culture. Furthermore, after ex vivo treatment of native atherosclerotic plaques obtained during open carotid endarterectomy surgery, Fe@C NPs penetrated the inner structures and caused structural changes of atherosclerotic plaques, depending on the period of implantation in Wistar rats, serving as a natural bioreactor. The high biocompatibility of the Fe@C NPs shows great potential in the treatment of atherosclerosis disease as an active substance of stent coatings to prevent restenosis and the formation of atherosclerotic plaques.